COVER CROPS AS A WEED CONTROL METHOD AND THEIR EFFECT ON THE INITIAL GROWTH OF A Tectona grandis L.f. PLANTATION - Guevara Bonilla, Mario; Briceño Elizondo, Elemer; Esquivel Segura, Edwin Antonio; Arguedas, Marcela; Arias Aguilar, Dagoberto (Floresta, 2020)
Tectona grandis L.f. (teak), is one of the most used tropical species in commercial reforestation projects. Weed control is a common activity within these plantations. The objective of the study was to evaluate the effect of cover crops in weed control and the initial growth of a young teak stand in the southern part of Costa Rica. We used a randomized complete blocks design with three replications and seven treatments: a) control (without weed control), b) chemical weed control, c) manual weed control, d) cover crop Canavalia ensiformis, e) cover crop Vigna radiata, f) mix between Vigna radiata and Pueraria phaseloides, g) cover crop Crotalaria juncea. In addition, we calculated total costs for all treatments. All species exceeded 60% ground coverage, with C. juncea and V. radiata being the best performers. Although all cover crops had higher height values than the other treatments, only C. ensiformis had a significant effect on height growth at 6 months of age. Manual weed control was the most economical treatment. Based on the results obtained, we concluded that the cover crops can be used as an alternative method of weed control without affecting the growth of the trees.